Translation in Semantically-Restricted and Professional Domains: In Search of a Theory—Editorial to Ril 18. - Witczak-Plisiecka, Iwona; Platonova, Marina (Research in Language, 2020)
This paper comments on selected problems related to the theory and practice of translation in various professional, and other semantically-restricted domains. The text introduces a selection of papers published in Research in Language, Vol. 18, No. 3, which together with a number of papers published in RiL earlier issues collectively present various research programmes which link translation and specialised discourses. The field of specialised languages is constantly growing, including new professional varieties and new approaches. There are numerous publications and journals focusing on LSP problems, as well as conferences which offer fora for relevant discussions. Selected articles in the volume originated from conference meetings “Meaning in Translation,” held in Riga, Latvia. The present paper comments on selected approaches to semantically-restricted domains in translation and features of specialised and professional discourses.